Positive electrode active material, positive electrode, and rechargeable lithium battery
By using lithium nickel-manganese composite oxides and lithium transition metal phosphates and other materials, the problem of shortage of cobalt supply in the positive electrode active substances of lithium batteries is solved, and a lithium battery with high energy density and long cycle life is achieved.
Patent Information
- Application Number
- CN202411056616.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-03
- Filing Date
- 2024-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
The active substances of existing lithium batteries contain cobalt, which leads to shortage of supply and increased costs, making it difficult to develop lithium batteries with high energy density and long cycle life.
Li-nickel-manganese composite oxides are used as positive electrode active substances. By adjusting the content and particle size of nickel and manganese, combined with the use of lithium transition metal phosphate, an efficient positive electrode material is formed.
It realizes the reduction of positive electrode material costs, ensures high capacity and high energy density characteristics, and suppresses side reactions at high voltages and extends cycle life.
Smart Images

Figure CN119447219A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present disclosure described herein relate to positive electrode active materials, positive electrodes, and rechargeable lithium batteries. Background Art
[0002] Portable information devices such as mobile phones, laptop computers, smart phones, etc. and / or vehicles (e.g., electric vehicles, hybrid vehicles, etc.) have used rechargeable lithium batteries with relatively high energy density and relative portability as driving power sources for portable information devices and / or vehicles. Recently, research has been actively conducted to use rechargeable lithium batteries with relatively high energy density as driving power sources and / or power storage power sources (e.g., for power walls) for hybrid vehicles or electric vehicles.
[0003] Various positive electrode active materials have been studied to realize the application of rechargeable lithium batteries for the purposes described. Among them, lithium nickel oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides and / or lithium cobalt oxides are mainly used as positive electrode active materials. However, although the demand for large-size, high-capacity or high-energy-density rechargeable lithium batteries has increased recently, the supply of positive electrode active materials containing cobalt (a rare metal) is expected to be in serious shortage (e.g., supply shortage). In other words, because cobalt is expensive and lacks remaining or large reserves, it is necessary or desirable to develop positive electrode active materials that do not contain cobalt or use cobalt in a reduced amount. Summary of the invention
[0004] Aspects according to one or more embodiments relate to a positive electrode active material including a lithium nickel manganese composite oxide, and a positive electrode and a rechargeable lithium battery including the same, wherein the positive electrode active material innovatively reduces the price of the positive electrode material while ensuring high capacity and high energy density characteristics, and improves high voltage performance by inhibiting or reducing side reactions with an electrolyte at high voltage.
[0005] Aspects according to one or more embodiments relate to a positive electrode active material that maximizes capacity while minimizing or reducing production costs, ensures long cycle life characteristics at high voltages, and inhibits side reactions with electrolytes. A rechargeable lithium battery using the positive electrode active material can exhibit high initial charge / discharge capacity and efficiency even under high voltage operating conditions, and can achieve long cycle life characteristics.
[0006] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the presented embodiments of the disclosure.
[0007] In some embodiments, the positive electrode active material includes: a first positive electrode active material including a lithium nickel manganese-based composite oxide having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on about 100 mol% of the total amount of metals other than lithium and including (e.g., each) secondary particles made by aggregating a plurality of primary particles (e.g., in the form of secondary particles), wherein the average particle size (D 50 ) is about 10 μm to about 20 μm; a second positive electrode active material, which includes a lithium nickel manganese composite oxide, the lithium nickel manganese composite oxide has a nickel content (e.g., amount) greater than or equal to about 60 mol% based on about 100 mol% of the total amount of metals other than lithium and includes single particles (e.g., in the form of single particles) (e.g., each is a monolithic particle), wherein the average particle size (D 50 ) is about 2 μm to about 8 μm; and a third positive electrode active material comprising particles including a lithium transition metal phosphate (eg, in the form of particles including a lithium transition metal phosphate).
[0008] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material.
[0009] In some embodiments, a rechargeable lithium battery includes the aforementioned positive electrode, negative electrode, and electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 is a schematic diagram schematically illustrating a rechargeable lithium battery according to some embodiments.
[0011] Figure 2 1 is a scanning electron microscope (SEM) image of the first positive electrode active material of Example 1.
[0012] Figure 3 : is a SEM image of the second positive electrode active material of Example 1.
[0013] Figure 4 is a SEM image of the third positive electrode active material of Example 1.
[0014] Figure 5 This is a SEM image of the third positive electrode active material of Example 2.
[0015] Description of Reference Numerals
[0016] 100: Rechargeable lithium battery 10: Positive electrode
[0017] 20: Negative electrode 30: Separator
[0018] 40: electrode assembly 50: shell DETAILED DESCRIPTION
[0019] Hereinafter, specific embodiments will be described in more detail so that those skilled in the art can easily implement them. However, the present disclosure may be implemented in many different forms and is not to be construed as limited to the example embodiments set forth herein.
[0020] The terms used herein are for describing the embodiments only and are not intended to limit the present disclosure. A singular expression includes a plural expression unless the context clearly indicates otherwise.
[0021] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like, of the components.
[0022] In this document, it should be understood that terms such as "comprising", "including" or "having" are intended to indicate the existence of the implemented aspects, features, quantities, operations, elements and / or their (e.g., any appropriate) combinations thereof, but do not exclude the possibility of the existence or addition of one or more other aspects, features, quantities, operations, elements and / or their (e.g., any appropriate) combinations thereof.
[0023] As used herein, expressions such as “at least one of,” “one of,” and “selected from,” when preceding or following a list of elements, modify the entire list of elements and do not modify the individual elements of the list. For example, “at least one of a, b, and c,” “at least one selected from a, b, and c,” and the like may indicate only a, only b, only c, both a and b (e.g., simultaneously), both a and c (e.g., simultaneously), b and c (e.g., simultaneously), all of a, b, and c, or variations thereof.
[0024] In the accompanying drawings, for clarity, the thickness of layers, films, panels, regions, etc. is exaggerated, and the same reference numerals represent the same elements throughout, and repeated descriptions thereof may not be provided in the specification. It will be understood that if (for example, when) an element (such as a layer, film, region, or substrate) is referred to as being "on" another element (such as a layer, film, region, or substrate), it may be directly on the other element (such as a layer, film, region, or substrate) or there may also be intervening elements. In other examples, if (for example, when) an element is referred to as being "directly on" another element, there are no intervening elements.
[0025] In one or more embodiments, the “layer” herein includes not only a shape formed on the entire surface but also a shape formed on a partial surface if (for example, when) viewed from a plan view.
[0026] "Group" refers to a Group of the Periodic Table of the Elements according to the International Union of Pure and Applied Chemistry ("IUPAC") 1-18 Group grouping system.
[0027] In one or more embodiments, the average particle size can be measured by methods well known to those skilled in the art (e.g., by a particle size analyzer, or by a transmission electron microscope image or a scanning electron microscope image). In one or more embodiments, the average particle size value is obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles in each particle size range, and calculating therefrom. Unless otherwise specified, the average particle size (D 50 ) may refer to the diameter of particles having a cumulative volume of 50% by volume in a particle size distribution. If (for example, when) no additional definition is provided, the average particle size (D) as used herein is 50 ) refers to the diameter of particles accounting for 50% by volume of the cumulative volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscope image. In this specification, unless otherwise specified, when a particle is spherical, "diameter" indicates a particle diameter or an average particle diameter, and when a particle is non-spherical, "diameter" indicates a major axis length or an average major axis length.
[0028] In this document, "or" is not interpreted as an exclusive meaning. For example, "A or B" is interpreted to include A, B, A+B, etc.
[0029] The term "metal" is interpreted as a concept including ordinary metals, transition metals, and metalloids (semimetals).
[0030] As used herein, the term "substantially" and similar terms are used as terms of approximation and not as terms of degree, and are intended to account for the inherent deviations in measured or calculated values that one of ordinary skill in the art would recognize. Also, the term "about" and similar terms, when used herein in conjunction with a numerical value or range of values, include both the recited value and values within an acceptable range of deviation as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (e.g., limitations of the measurement system). For example, "about" may mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the recited value.
[0031] And, any numerical range set forth in this article is intended to include all sub-ranges of the same numerical precision included in the range of setting forth. For example, the range of "1.0 to 10.0" is intended to include all sub-ranges (and including end values) between the minimum value 1.0 set forth and the maximum value 10.0 set forth, that is, with a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as, for example, 2.4 to 7.6. Any maximum numerical limit set forth herein is intended to include all lower numerical limits contained therein, and any minimum numerical limit set forth in this specification is intended to include all higher numerical limits contained therein. Accordingly, the applicant reserves the right to modify this specification (including claims) to explicitly set forth any sub-ranges contained in the range explicitly set forth herein.
[0032] Hereinafter, a positive electrode active material and a rechargeable lithium battery according to example embodiments will be described in more detail.
[0033] Positive electrode active material
[0034] In some embodiments, the positive electrode active material includes: a first positive electrode active material including a lithium nickel manganese-based composite oxide having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on about 100 mol% of the total amount of metals other than lithium and including (e.g., each) secondary particles made by aggregating a plurality of primary particles (e.g., in the form of secondary particles), wherein the average particle size (D 50 ) is about 10 μm to about 20 μm; a second positive electrode active material, which includes a lithium nickel manganese composite oxide, the lithium nickel manganese composite oxide has a nickel content (e.g., amount) greater than or equal to about 60 mol% based on about 100 mol% of the total amount of metals other than lithium and includes individual particles (e.g., in the form of individual particles) (e.g., each is a monolithic particle), wherein the average particle size (D 50 ) is about 2 μm to about 8 μm; and a third positive electrode active material comprising particles including a lithium transition metal phosphate (eg, in the form of particles including a lithium transition metal phosphate).
[0035] Due to the recent sharp rise in the price of cobalt (a rare metal), there is a need to develop positive electrode active materials that do not contain cobalt or reduce its content (e.g., amount). Among them, spinel crystal structures (such as lithium manganese oxide (LMO) and the like) are limited in achieving high capacity due to the small available lithium capacity in the structure. Due to the high available lithium capacity in the structure, the layered nickel manganese positive electrode active material has excellent or appropriate capacity and efficiency characteristics, making it suitable as a material for high-capacity batteries. However, when cobalt, which plays a key role in the layered structure, is removed, the structural stability is reduced, the resistance is increased, and it is difficult to ensure long cycle life characteristics. In one or more embodiments, the layered nickel manganese positive electrode active material that does not contain cobalt may instead have the problem of accelerating side reactions with the electrolyte under high voltage and high temperature conditions, thereby increasing gas generation and deteriorating cycle life characteristics.
[0036] In some embodiments, a first positive electrode active material comprising a lithium nickel manganese-based composite oxide including secondary particles having an average particle size of about 10 micrometers (μm) to about 20 μm (e.g., in the form of secondary particles) is mixed with a second positive electrode active material comprising a lithium nickel manganese-based composite oxide including single particles having an average particle size of about 2 μm to about 8 μm (e.g., in the form of single particles), and a third positive electrode active material comprising a lithium transition metal phosphate as a low-cost material is added thereto, thereby proposing a positive electrode active material that exhibits improved high voltage performance and achieves high capacity, high energy density, and long cycle life characteristics.
[0037] The average particle size (D 50 ) may be larger than the average particle size (D 50 ). Herein, the first positive electrode active material may be represented as large particles, and the second positive electrode active material may be represented as small particles. The average particle size (D 50 ) may be larger than the average particle size of a single particle of the third positive electrode active material. Large particles in the form of secondary particles and small particles in the form of single particles are appropriately mixed as lithium nickel manganese-based oxides, and then further mixed with lithium transition metal phosphates to maximize or increase capacity and energy density and improve high voltage characteristics.
[0038] In this paper, the average particle size (D 50 ) refers to the diameter of particles accounting for 50 volume % of the cumulative volume in a particle size distribution obtained by randomly measuring the sizes (diameters or major axis lengths) of about 20 particles in a scanning electron microscope image of a positive electrode active material.
[0039] The average particle size (D 50) may be, for example, about 10 μm to about 18 μm or about 12 μm to about 16 μm. The average particle size (D 50 ) may be, for example, about 2 μm to about 7 μm, about 2.5 μm to about 6 μm, or about 3 μm to about 5 μm. The particles of the third positive electrode active material may be one type or kind of primary particles, and their average particle size (D 50 ) may be, for example, about 10 nm to about 2 μm, such as about 50 nm to about 1.5 μm, about 100 nm to about 1.0 μm, about 100 nm to about 900 nm, or about 100 nm to about 600 nm. If the average particle size of each positive electrode active material satisfies the above range, high capacity can be achieved, and energy density can be maximized or increased.
[0040] Based on a total of about 100wt% of the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material, the first positive electrode active material may be included in an amount of about 60wt% to about 90wt%, the second positive electrode active material may be included in an amount of about 5wt% to about 35wt%, and the third positive electrode active material may be included in an amount of about 5wt% to about 35wt%. As a specific example, the first positive electrode active material may be included in an amount of about 60wt% to about 85wt%, the second positive electrode active material may be included in an amount of about 10wt% to about 25wt%, and the third positive electrode active material may be included in an amount of about 5wt% to about 20wt%. If the mixing ratio of each positive electrode active material satisfies the above range, the energy density can be further increased while increasing the capacity.
[0041] The lithium nickel manganese composite oxide of the first positive electrode active material and the lithium nickel manganese composite oxide of the second positive electrode active material may be the same or different from each other. In each lithium nickel manganese composite oxide, based on the total amount of metals other than lithium in the lithium nickel manganese composite oxide of about 100mol%, the nickel content (e.g., amount) may be greater than or equal to about 60mol%, such as about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If the nickel content (e.g., amount) satisfies the above range, even if the cobalt content (e.g., amount) is reduced, high capacity can be achieved and structural stability can be increased.
[0042] For example, in the lithium nickel manganese composite oxide, based on the total amount of metals other than lithium of about 100mol%, the manganese content (e.g., amount) may be, for example, about 10mol% to about 40mol%, such as about 10mol% to about 39mol%, about 10mol% to about 35mol%, about 10mol% to about 30mol%, about 10mol% to about 29mol%, about 15mol% to about 39mol%, about 20mol% to about 39mol% or about 20mol% to about 30%. If the manganese content (e.g., amount) satisfies the above range, the positive electrode active material can improve structural stability while achieving high capacity.
[0043] In each of the first positive electrode active material and the second positive electrode active material, the lithium nickel manganese composite oxide may be a lithium nickel manganese aluminum composite oxide further including aluminum in addition to nickel and manganese. When the lithium nickel manganese composite oxide includes aluminum, it is advantageous to maintain a stable layered structure even if the structure does not contain cobalt elements. The aluminum content (e.g., amount) in the lithium nickel manganese aluminum composite oxide based on about 100mol% of the total amount of metals other than lithium may be greater than or equal to about 0.1mol%, greater than or equal to about 0.5mol%, or greater than or equal to about 1mol%, such as about 1mol% to about 3mol%, about 1mol% to about 2.5mol%, about 1mol% to about 2mol%, or about 1mol% to about 1.9mol%. If the aluminum content (e.g., amount) satisfies the above range, even if cobalt is not contained, a stable layered structure can be maintained, the problem of structural collapse caused by charging and discharging can be suppressed or reduced, and the long cycle life characteristics of the positive electrode active material can be achieved.
[0044] The lithium nickel manganese-based composite oxide of the first positive electrode active material and the lithium nickel manganese-based composite oxide of the second positive electrode active material may each be independently represented by Chemical Formula 1.
[0045] Chemical formula 1
[0046] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1
[0047] In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1is (for example, selected from) one or more elements of B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is (for example, selected from) one or more elements of F, P and S.
[0048] In Chemical Formula 1, 0.9≤a1≤1.5 or 0.9≤a1≤1.2. In addition, Chemical Formula 1 may contain aluminum, wherein 0.6≤x1≤0.8, 0.1≤y1≤0.39, 0.01≤z1≤0.03, and 0≤w1≤0.29 may be satisfied, and for example, 0.6≤x1≤0.8, 0.1≤y1≤0.39, 0.01<z1≤0.03, and 0≤w1≤0.29 may be satisfied.
[0049] In Chemical Formula 1, for example, 0.6≤x1≤0.79, 0.6≤x1≤0.78, 0.6≤x1≤0.75, 0.65≤x1≤0.8, or 0.7≤x1≤0.79; 0.1≤y1≤0.35, 0.1≤y1≤0.30, 0.1≤y1≤0.29, 0.15≤y1≤0.39, or 0.2≤y1≤0.3; 0.01≤z1≤0.025, 0 .01<z1≤0.02 or 0.01<z1≤0.019; and 0≤w1≤0.28, 0≤w1≤0.27, 0≤w1≤0.26, 0≤w1≤0.25, 0≤w1≤0.24, 0≤w1≤0.23, 0≤w1≤0.22, 0≤w1≤0.21, 0≤w1≤0.2, 0≤w1≤0.15, 0≤w1≤0.1 or 0≤w1≤0.09.
[0050] The lithium nickel manganese composite oxide may be a cobalt-free compound that does not include cobalt or includes a very small amount of cobalt. For example, the lithium nickel manganese composite oxide of the first positive electrode active material and the lithium nickel manganese composite oxide of the second positive electrode active material each independently have a cobalt content (e.g., amount) of about 0 mol% to about 0.01 mol% based on about 100 mol% of the total amount of metals other than lithium.
[0051] First positive electrode active material
[0052] In some embodiments, the secondary particles of the first positive electrode active material not including the coating may include aluminum at a substantially uniform concentration. In other words, the aluminum is uniformly (substantially uniformly) dispersed in the particles, with no concentration gradient from the center to the surface of each particle, or no concentration difference between the inside and outside of the particles. Accordingly, the positive electrode active material can be prepared by using an aluminum raw material to prepare a precursor without additional doping with aluminum, wherein a nickel-manganese-aluminum hydroxide can be used as a precursor and a composite oxide is synthesized. In other words, regardless of the position of the primary particles, the aluminum content (e.g., amount) inside the primary particles may be equal or similar. If the primary particles are selected at random positions in the cross section of the secondary particles, and the aluminum content (e.g., amount) is measured inside the primary particles rather than at their interfaces, the aluminum content (e.g., amount) may be the same / similar / substantially uniform regardless of the position of the primary particles, that is, whether the primary particles are close to the center of the secondary particles or close to the surface. In this structure, even if cobalt is absent or present in a very small amount, a stable layered structure can be maintained and aluminum byproducts or aluminum aggregates are not generated, thereby simultaneously improving the capacity, efficiency, and cycle life characteristics of the positive electrode active material.
[0053] The first positive electrode active material according to some embodiments may further include a coating containing aluminum and zirconium on the surface of the secondary particles. The first positive electrode active material includes an aluminum-zirconium-rich layer on the surface of the secondary particles to effectively inhibit or reduce side reactions with the electrolyte at high voltages, thereby improving capacity and cycle life characteristics at high voltages.
[0054] The coating of the first positive electrode active material may have an aluminum content (e.g., amount) of about 0.1 mol% to about 2 mol% based on about 100 mol% of the total amount of metals other than lithium, and the coating may have a zirconium content (e.g., amount) of about 0.05 mol% to about 1 mol%. In the first positive electrode active material, the coating may have an aluminum content (e.g., amount) of, for example, about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol% based on about 100 mol% of the total amount of metals other than lithium. The aluminum or zirconium content (e.g., amount) in the coating may be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. If the aluminum content (e.g., amount) in the coating satisfies the above range, the coating can be formed to have a substantially uniform and thin thickness, which will not increase the resistance of the positive electrode active material and will effectively inhibit or reduce side reactions with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery at high voltage.
[0055] In the first positive electrode active material, the zirconium content (e.g., amount) of the coating may be, for example, about 0.1 mol% to about 1 mol%, about 0.1 mol% to about 0.9 mol%, about 0.1 mol% to about 0.8 mol%, or about 0.1 mol% to about 0.6 mol%. If the zirconium content (e.g., amount) satisfies the above range, a satisfactory coating can be formed without deteriorating the capacity of the positive electrode active material or increasing the resistance, and effectively inhibiting or reducing the side reaction with the electrolyte, and further improving the capacity characteristics and cycle life characteristics under high voltage operating conditions.
[0056] The coating layer of the first positive electrode active material may further include yttrium in addition to aluminum and zirconium, wherein the content (eg, amount) of yttrium may be about 0.05 mol % to about 1 mol % based on about 100 mol % of the total amount of metals other than lithium in the first positive electrode active material.
[0057] The coating of the first positive electrode active material may include a film (e.g., in the form of a film) that continuously surrounds the surface of the secondary particle, for example, may include a shell (e.g., in the form of a shell) that surrounds the entire surface of the secondary particle. This is different from a structure in which only a portion of the surface of the secondary particle is partially coated. According to some embodiments, the coating may be formed to completely cover the surface of the secondary particle, and may be formed to be very thin and substantially uniform in thickness, so that the positive electrode active material does not increase resistance or reduce capacity, improves structural stability, effectively inhibits side reactions with the electrolyte, reduces the amount of gas generated under high voltage and high temperature conditions, and achieves long cycle life characteristics.
[0058] The thickness of the coating of the first positive electrode active material may be about 30 nanometers (nm) to about 500nm, such as about 30nm to about 450nm, about 30nm to about 400nm, about 30nm to about 350nm, about 30nm to about 300nm, about 30nm to about 250nm, about 30nm to about 200nm, about 30nm to about 150nm, about 50nm to about 500nm, about 80nm to about 500nm or about 100nm to about 500nm. When the coating meets these thickness ranges, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating, and the side reaction with the electrolyte can be effectively suppressed or reduced. The thickness of the coating can be measured by, for example, TOF-SIMS, XPS or EDS analysis, and the thickness range of the coating can be measured by TEM-EDS line profile.
[0059] The coating of the first positive electrode active material may be thin and substantially uniform in thickness, ranging from tens of nanometers to hundreds of nanometers. For example, the deviation of the coating thickness in a positive electrode active material particle may be less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the deviation of the coating thickness refers to the deviation of the coating thickness in a positive electrode active material particle. For example, the thickness of about 10 points in the electron microscope image of the cross section of a single positive electrode active material particle can be measured to calculate the arithmetic mean, and then the absolute value of the difference between a measured data and the arithmetic mean is divided by the arithmetic mean and multiplied by 100 to calculate the deviation of the coating thickness. The fact that the deviation or standard deviation of the coating thickness meets the above range indicates that a coating with substantially uniform thickness is well formed in the form of a film on the surface of the positive electrode active material particle. Accordingly, the structural stability of the positive electrode active material is improved, the side reaction with the electrolyte is effectively suppressed or reduced, and the resistance increase or capacity reduction caused by the coating can be minimized or reduced.
[0060] In one or more embodiments, during the coating formation process, aluminum may diffuse into the secondary particles. Accordingly, the positive electrode active material according to some embodiments may further include a grain boundary coating portion, which includes aluminum and is arranged on the surface of the primary particles in the interior of the secondary particles. The interior of the secondary particle may refer to the entire interior except the surface of the secondary particle, or may be a zone of about 60% of the radius of the secondary particle (i.e., the distance from the surface of the secondary particle to the center of the secondary particle) from the center of the secondary particle toward the surface of the secondary particle. The grain boundary coating is a different concept from the coating on the surface of the secondary particle, and refers to the coating portion formed on the surface of the primary particle inside the secondary particle. The presence of the grain boundary coating portion can be confirmed by SEM-EDS analysis of the cross section of the positive electrode active material. By forming (or providing) an aluminum grain boundary coating portion, the positive electrode active material can become more structurally stable, and its cycle life characteristics can be improved.
[0061] The aluminum content (eg, amount) in the grain boundary coating portion is not particularly limited, and, for example, the aluminum content (eg, amount) in the grain boundary coating portion may be smaller than the aluminum content (eg, amount) in the coating layer.
[0062] On the other hand, the aluminum content (e.g., amount) of the coating of the first positive electrode active material may be greater than the aluminum content of the coating of the second positive electrode active material, which will be described in more detail later. For example, the aluminum content (e.g., amount) of the coating of the first positive electrode active material and the aluminum content (e.g., amount) of the coating of the second positive electrode active material may have a molar ratio of about 5:1 to about 2:1 or about 4:1 to about 2:1. In this article, the aluminum of the coating in the first positive electrode active material and the second positive electrode active material may not act as a resistor, and maximize or increase the capacity and cycle life characteristics at high voltage and improve the structural stability of each layer.
[0063] Second positive electrode active material
[0064] A single particle of the second positive electrode active material refers to a single particle that exists alone without a grain boundary within the particle, is composed of one particle, and has a single particle, a monolithic structure, an integral structure, or a non-aggregated particle in which the particles are not aggregated with each other in morphology and exist as independent phases, and can be expressed as a single particle (integral particle, single grain), such as a single crystal.
[0065] The second positive electrode active material further includes a coating layer containing aluminum on the surface of the single particle. In this case, the initial discharge capacity at high voltage and the cycle life characteristics can be improved.
[0066] The aluminum content (e.g., amount) in the coating of the second positive electrode active material may be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%, based on about 100 mol% of the total amount of metals other than lithium in the second positive electrode active material. This refers only to the aluminum content (e.g., amount) included in the coating, and does not include the aluminum content (e.g., amount) included in a single particle. The aluminum content (e.g., amount) in the coating can be measured, for example, by SEM-EDS analysis of the surface or cross-section of the positive electrode active material. When the aluminum content (e.g., amount) in the coating satisfies the above range, the coating may have a substantially uniform and thin thickness, which does not increase the resistance of the positive electrode active material and effectively inhibits or reduces side reactions with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery under high voltage and high temperature conditions. For example, if the aluminum content (e.g., amount) of the coating is too much, a substantially uniform coating may not be formed or resistance may increase, which may reduce charge / discharge efficiency and cycle life characteristics, and if the aluminum content (e.g., amount) of the coating is too little, a coating of a suitable or appropriate thickness may not be formed and the effect of suppressing or reducing side reactions with the electrolyte may be reduced.
[0067] The coating of the second positive electrode active material may further include yttrium, and in this case, the side reaction between the positive electrode active material and the electrolyte can be effectively suppressed or reduced at high voltage, thereby improving the cycle life characteristics. The yttrium content (e.g., amount) in the coating may be about 0.1 mol% to about 1 mol%, such as about 0.1 mol% to about 0.9 mol%, about 0.1 mol% to about 0.8 mol%, about 0.1 mol% to about 0.6 mol%, about 0.1 mol% to about 0.4 mol% or about 0.1 mol% to about 0.3 mol%. If the yttrium content (e.g., amount) satisfies the above range, the positive electrode active material forms a good or appropriate coating without reducing capacity or increasing resistance, effectively suppressing or reducing side reactions with the electrolyte, and effectively reducing the amount of gas generated under high voltage or high temperature conditions.
[0068] The coating of the second positive electrode active material may include a film (e.g., in the form of a film) that continuously surrounds the surface of a single particle, or may include, for example, a shell (e.g., in the form of a shell) that surrounds the entire surface of a single particle. This is different from a structure in which only a portion of the particle surface is partially coated. The coating according to some embodiments may be formed to have a very thin and substantially uniform thickness and completely cover the surface of a single particle, which neither increases the resistance of the positive electrode active material nor degrades the capacity, and exhibits improved structural stability, and can effectively inhibit or reduce side reactions with the electrolyte, thereby achieving long cycle life characteristics at high voltage.
[0069] The thickness of the coating of the second positive electrode active material may be about 30nm to about 500nm, such as about 30nm to about 450nm, about 30nm to about 400nm, about 30nm to about 350nm, about 30nm to about 300nm, about 30nm to about 250nm, about 30nm to about 200nm, about 30nm to about 150nm, about 50nm to about 500nm, about 80nm to about 500nm or about 100nm to about 500nm. If the coating meets these thickness ranges, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating, and the side reaction with the electrolyte can be effectively suppressed or reduced. The thickness of the coating can be measured by, for example, TOF-SIMS, XPS or EDS analysis, and the thickness range of the coating can be measured by TEM-EDS line profile.
[0070] The coating of the second positive electrode active material can be thin, and the thickness is substantially uniform, at the level of tens of nanometers to hundreds of nanometers. For example, the deviation of the coating thickness in a positive electrode active material particle may be less than or equal to about 20%, less than or equal to about 18% or less than or equal to about 15%. In this article, the deviation of the coating thickness refers to the deviation of the coating thickness in a positive electrode active material particle. For example, the thickness of about 10 points in the electron microscope image of the cross section of a single positive electrode active material particle can be measured to calculate the arithmetic mean, and then the absolute value of the difference between a measured data and the arithmetic mean is divided by the arithmetic mean and multiplied by 100 to calculate the deviation of the coating thickness. The fact that the deviation or standard deviation of the coating thickness meets the above range indicates that a coating with substantially uniform thickness is well formed (or provided) in the form of a film on the surface of the positive electrode active material particle. Accordingly, the structural stability of the positive electrode active material is improved, the side reaction with the electrolyte can be effectively suppressed or reduced, and the resistance increase or capacity reduction caused by the coating can be minimized or reduced.
[0071] In the coating layer of the second positive electrode active material, aluminum may include a substantially continuous film (eg, exist in the form of a substantially continuous film) and yttrium may include an island shape (eg, exist in the form of an island shape) due to characteristics of each element.
[0072] In some embodiments, aluminum and yttrium may be mixed in one coating, wherein the aluminum may include a substantially continuous film (eg, present in the form of a film) and the yttrium may include an island shape (eg, present in the form of an island shape), but the present disclosure is not limited thereto.
[0073] In some embodiments, aluminum and yttrium may each form (or provide) a separate layer. For example, the second positive electrode active material includes: a first coating containing aluminum and arranged on the surface of a single particle; and a second coating containing yttrium and arranged on the first coating. Aluminum is first attached or absorbed on the surface of a single particle to form (or provide) a first coating in the form of a thin film, and yttrium is coated thereon to form (or provide) a second coating. In this article, aluminum and yttrium are mixed in the first coating and the second coating, but the first coating may be an aluminum-rich coating containing aluminum as a main component, and the second coating may be a yttrium-rich coating containing yttrium as a main component. In this article, in the second coating, yttrium may exist in an island shape, but is not particularly limited thereto.
[0074] The thickness of the first coating and the second coating is not particularly limited. However, the thickness of the first coating may be about 10nm to about 200nm, such as about 20nm to about 200nm, about 30nm to about 200nm, or about 30nm to about 180nm. The thickness of the second coating may be about 20nm to about 300nm, such as about 20nm to about 250nm, about 20nm to about 200nm, about 30nm to about 300nm, or about 50nm to about 300nm. When the respective thicknesses meet the above ranges, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to the coating, and the cycle life characteristics under high voltage can be improved by effectively suppressing or reducing side reactions with the electrolyte.
[0075] The third positive electrode active material
[0076] The lithium transition metal phosphate of the third positive electrode active material may include, for example, lithium iron phosphate, lithium manganese iron phosphate, lithium manganese phosphate, lithium titanium phosphate, and / or (eg, any appropriate) combinations thereof.
[0077] The lithium transition metal phosphate of the third positive electrode active material may be represented by Chemical Formula 3, Chemical Formula 4, Chemical Formula 5, Chemical Formula 6, or Chemical Formula 7.
[0078] Chemical formula 3
[0079] Li a3 Fe (1-x3) M 3 x3 PO4
[0080] In Chemical Formula 3, 0.90≤a3≤1.5, 0≤x3≤0.4, and M 3 It is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr and / or (e.g., any suitable) combination thereof.
[0081] The compound represented by Chemical Formula 3 may be lithium iron phosphate. In Chemical Formula 3, for example, 0.90≤a3≤1.2 or 0.95≤a3≤1.1, and 0≤x3≤0.3, 0≤x3≤0.2, 0≤x3≤0.1 or 0<x3≤0.05. For example, if (for example, when) a3=1 and x3=0, Chemical Formula 3 may be represented as LiFePO4.
[0082] Chemical formula 4
[0083] Li a4 Mn x4 Fe (1-x4-y4) M 4 y4 PO4
[0084] In Chemical Formula 4, 0.90≤a4≤1.5, 0.1≤x4≤0.9, 0≤y4≤0.4, and M 4 It is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr and / or (e.g., any suitable) combination thereof.
[0085] The compound represented by Chemical Formula 4 may be lithium manganese iron phosphate. In Chemical Formula 4, for example, 0.90≤a4≤1.2 or 0.95≤a4≤1.1, and 0.2≤x4≤0.8, 0.3≤x4≤0.7 or 0.4≤x4≤0.6. The compound represented by Chemical Formula 4 may be, for example, LiMn 0.9 Fe 0.1 PO4、LiMn 0.8 Fe 0.2 PO4、LiMn 0.7 Fe 0.3 PO4、LiMn 0.6 Fe 0.4 PO4、LiMn 0.5 Fe 0.5 PO4、LiMn 0.4 Fe 0.6 PO4、LiMn 0.3 Fe 0.7 PO4、LiMn 0.2 Fe 0.8 PO4 or LiMn 0.1 Fe 0.9 PO4.
[0086] Chemical formula 5
[0087] Li a5 Mn (1-x5) M 5 x5 PO4
[0088] In Chemical Formula 5, 0.90≤a5≤1.5, 0≤x5≤0.4, and M 5 It is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr and / or (e.g., any suitable) combination thereof.
[0089] The compound represented by Chemical Formula 5 may be lithium manganese phosphate. In Chemical Formula 5, for example, 0.90≤a5≤1.2 or 0.95≤a5≤1.1, and 0≤x5≤0.3, 0≤x5≤0.2, 0≤x5≤0.1 or 0<x5≤0.05. For example, if (for example, when) a5=1 and x5=0, Chemical Formula 5 may be represented as LiMnPO4.
[0090] Chemical formula 6
[0091] Li a6 Ti (2-x6) M 6 x6 (PO4)3
[0092] In Chemical Formula 6, 0.90≤a6≤1.5, 0≤x6≤0.4, and M 6 It is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr and / or (e.g., any suitable) combination thereof.
[0093] The compound represented by Chemical Formula 6 may be lithium titanium phosphate. In Chemical Formula 6, for example, 0.90≤a6≤1.2 or 0.95≤a6≤1.1, and 0≤x6≤0.3, 0≤x6≤0.2, 0≤x6≤0.1 or 0<x6≤0.05. For example, if (for example, when) a6=1 and x6=0, Chemical Formula 6 may be represented as LiTi2(PO4)3.
[0094] Chemical formula 7
[0095] Li a7 Ti (1-x7) M 7 x7 PO5
[0096] In Chemical Formula 7, 0.90≤a7≤1.5, 0≤x7≤0.4, and M 7 It is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr and / or (e.g., any suitable) combination thereof.
[0097] The compound represented by Chemical Formula 7 may be lithium titanium phosphate. In Chemical Formula 7, for example, 0.90≤a7≤1.2 or 0.95≤a7≤1.1, and 0≤x7≤0.3, 0≤x7≤0.2, 0≤x7≤0.1, or 0<x7≤0.05. For example, if (for example, when) a7=1 and x7=0, Chemical Formula 7 may be represented as LiTiPO5.
[0098] As a specific example, the lithium transition metal phosphate of the third positive electrode active material may be LiFePO4, LiMn 0.7 Fe 0.3 PO4、LiMn 0.6 Fe 0.4 PO4、LiMn 0.5 Fe 0.5 PO4、LiMn0.4 Fe 0.6 PO4、LiMn 0.3 Fe 0.7 PO4, LiMnPO4, LiTiPO5, LiTi2(PO4)3 and / or (e.g., any suitable) combinations thereof.
[0099] In the positive electrode active material according to some embodiments, the cobalt content (e.g., amount) may be, for example, less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol% (e.g., about 0 mol% to about 0.01 mol%) based on about 100 mol% of the total amount of metals other than lithium. The positive electrode active material according to some embodiments may be, for example, a cobalt-free positive electrode active material.
[0100] In addition, in some embodiments, another positive electrode active material may not include (e.g., may exclude) sodium. Generally speaking, sodium ions can be used in the preparation process of the positive electrode active material, but according to the preparation method described in more detail later, positive electrode active material particles having a stable structure and a coating layer with substantially uniform thickness can be formed without using sodium ions.
[0101] Method for preparing positive electrode active material
[0102] In some embodiments, a method for preparing a positive electrode active material includes: (i) mixing a nickel-manganese composite hydroxide having a total nickel content (e.g., amount) greater than or equal to about 60 mol% based on about 100 mol% of the metal with a lithium raw material, and heat treating it to prepare a first positive electrode active material in the form of secondary particles made by aggregating multiple primary particles; (ii) mixing a nickel-manganese composite hydroxide having a total nickel content (e.g., amount) greater than or equal to about 60 mol% based on about 100 mol% of the metal with a lithium raw material, and heat treating the mixture to prepare a second positive electrode active material in the form of a single particle; (iii) preparing a third positive electrode material including a lithium transition metal phosphate; and (iv) mixing the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material.
[0103] In the process of preparing the first positive electrode active material and the second positive electrode active material, the nickel-manganese composite hydroxide may not include (for example, may exclude) cobalt or may include a very small amount of cobalt, and may be, for example, a cobalt-free nickel-manganese composite hydroxide. For example, it may be a cobalt-free nickel-manganese-aluminum composite hydroxide. The nickel-manganese composite hydroxide can be prepared by a general coprecipitation method.
[0104] The total amount of nickel content based on about 100mol% of metal in the nickel-manganese composite hydroxide can be greater than or equal to about 60mol%, such as about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. When the nickel content (e.g., amount) satisfies the above range, even if the cobalt content (e.g., amount) is reduced, high capacity can be achieved and structural stability can be increased.
[0105] The manganese content (e.g., amount) in the nickel-manganese composite hydroxide based on about 100 mol% of the total amount of metal can be about 10 mol% to about 40 mol%, about 10 mol% to about 39 mol%, about 10 mol% to about 35 mol%, about 10 mol% to about 30 mol%, about 10 mol% to about 29 mol%, about 15 mol% to about 39 mol%, about 20 mol% to about 39 mol%, or about 20 mol% to about 30 mol%.
[0106] In one or more embodiments, if (for example, when) the nickel-manganese composite hydroxide further contains aluminum, then based on the total amount of about 100 mol% of the metal, the aluminum content (for example, amount) may be greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, such as about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 1.9 mol%. If the manganese content and aluminum content of the nickel-manganese composite hydroxide meet the above range, high capacity can be achieved, while the structural stability of the positive electrode active material can be increased, and the production price can be reduced to increase economic benefits.
[0107] In the nickel-manganese composite hydroxide, the cobalt content (e.g., amount) may be less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%, based on about 100 mol% of the total amount of metal. The nickel-manganese composite hydroxide can be said to be economical because it avoids the increase in unit cost caused by cobalt, maximizes capacity, and improves structural stability.
[0108] As an example, the nickel-manganese-based composite hydroxide may be represented by Chemical Formula 2.
[0109] Chemical formula 2
[0110] Ni x2 Mn y2 Al z2 M 2 w2 (OH)2
[0111] In Chemical Formula 2, 0.6≤x2≤0.8, 0.1≤y2≤0.4, 0≤z2≤0.03, 0≤w2≤0.3, and 0.9≤x2+y2+z2+w2≤1.1, and M 2 It is (for example, selected from) one or more elements of B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr.
[0112] In Chemical Formula 2, for example, 0.6≤x2≤0.8, 0.1≤y2≤0.39, 0.01≤z2≤0.03, and 0≤w2≤0.29.
[0113] In the preparation process of the first positive electrode active material, no additional aluminum is doped thereon, and an aluminum raw material is used to prepare a precursor of a nickel-manganese-aluminum composite hydroxide, in which aluminum is uniformly dispersed in the structure. This precursor can be used to prepare a positive electrode active material that can stably maintain a layered structure despite repeated charging and discharging without the presence of cobalt, in which no aluminum byproduct or aluminum aggregate is formed, thereby improving the capacity and efficiency characteristics and cycle life characteristics of the positive electrode active material.
[0114] In the preparation process of the first positive electrode active material, the nickel-manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of about 1:0.9 to about 1:1.8 (e.g., about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2). The heat treatment after mixing can be carried out under an oxygen atmosphere, for example, at a temperature range of about 750°C to about 950°C, about 780°C to about 900°C, or about 810°C to about 890°C for about 2 hours to about 20 hours or about 4 hours to about 12 hours. By heat treatment, a lithium nickel-manganese composite oxide can be obtained. The obtained nickel-manganese composite oxide may include about 60 mol% or more (e.g., about 60 mol% to about 80 mol%) of nickel based on the total amount of about 100 mol% of the metal, but may not include cobalt or include a very small amount of cobalt less than or equal to about 0.01 mol%.
[0115] The method for preparing a positive electrode active material according to some embodiments may further include obtaining a lithium nickel manganese composite oxide in the process of preparing a first positive electrode active material, and then coating the lithium nickel manganese composite oxide. The lithium nickel manganese composite oxide has a significantly different residual lithium content (e.g., amount) and different surface characteristics from oxides having other compositions (e.g., conventional nickel oxides such as lithium nickel cobalt manganese composite oxides or lithium nickel cobalt aluminum composite oxides, etc.), and conventional coating methods cannot successfully form (or provide) a good or appropriate coating in the form of a substantially uniform film thereon. In some embodiments, a method for improving high voltage characteristics by uniformly (substantially uniformly) forming (or providing) a very thin coating on the surface of a lithium nickel manganese composite oxide having a very small amount of cobalt and a nickel content (e.g., amount) greater than or equal to about 60 mol% is applied. For example, a coating according to some embodiments may be formed by adding and mixing an aluminum raw material to an aqueous solvent, adding and mixing a lithium nickel manganese composite oxide, and then drying and reheating the mixture. This may be referred to as a wet coating method.
[0116] The aqueous solvent may include distilled water, an alcohol solvent and / or its (e.g., any appropriate) combination. The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide and / or its (e.g., any appropriate) combination. For example, the aluminum raw material may include aluminum sulfate, and in this case, it is advantageous to form (or provide) a coating having a substantially uniform thickness on the surface of the lithium nickel manganese composite oxide particles. The aluminum content (e.g., amount) of the aluminum raw material can be designed to be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol% or about 0.8 mol% to about 1.3 mol% based on the total amount of metals other than lithium in the first positive electrode active material.
[0117] The solution obtained by mixing the aluminum raw material in an aqueous solvent may have a pH of about 1.5 to about 3.5 (e.g., about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2). The mixing and stirring of the lithium nickel manganese composite oxide and the aqueous solvent (in which the aluminum raw material is mixed) may be performed for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5 (e.g., about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0). If these conditions are met, it is advantageous to form (or provide) a coating having a substantially uniform thickness.
[0118] Reheating can be understood as a process of forming (or providing) a coating, and can be performed, for example, in an oxygen atmosphere at a temperature range of about 700°C to about 850°C, about 750°C to about 840°C, or about 800°C to about 830°C for about 2 hours to about 20 hours or about 3 hours to about 10 hours.
[0119] In order to coat zirconium in addition to aluminum, reheating can be performed by adding a zirconium raw material to the product obtained after drying. The zirconium raw material may be, for example, zirconium oxide, and the zirconium raw material may be added so that the zirconium content (e.g., amount) is about 0.05 mol% to about 1 mol% based on about 100 mol% of the total amount of metals other than lithium in the first positive electrode active material.
[0120] Similarly, in the process of preparing the second positive electrode active material, the nickel manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of about 1:0.9 to about 1:1.8 (e.g., about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2). After mixing, the heat treatment can be carried out under an oxygen atmosphere, for example, at about 750°C to about 950°C, about 780°C to about 900°C, or about 810°C to about 890°C for about 2 hours to about 20 hours or about 4 hours to about 12 hours. By heat treatment, a lithium nickel manganese composite oxide can be obtained. The obtained lithium nickel manganese composite oxide may include nickel in an amount greater than or equal to about 60 mol% (e.g., about 60 mol% to about 80 mol%) based on the total amount of about 100 mol% of the metal, but does not include cobalt or includes a very small amount of cobalt less than or equal to about 0.01 mol%. In order to obtain a lithium nickel manganese composite oxide in the form of a single particle, a pulverization process may be further included.
[0121] In the process of preparing the second positive electrode active material, after obtaining a single particle including a lithium nickel manganese composite oxide by mixing and heat treating the nickel manganese composite hydroxide and the lithium raw material, a coating process of the single particle may be further included. The coating of the aluminum of the second positive electrode active material in the form of a single particle may also adopt a wet coating method according to some embodiments to form a satisfactory coating in the form of a substantially uniform film. In other words, the lithium nickel manganese composite oxide in the form of a single particle is added to a solution in which the aluminum raw material is mixed in an aqueous solvent, and then dried and reheated to prepare the second positive electrode active material.
[0122] The aqueous solvent and the aluminum raw material may be independently the same as the aqueous solvent and the aluminum raw material described above. The aluminum content (e.g., amount) of the aluminum raw material may be designed to be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol% or about 0.8 mol% to about 1.3 mol% based on about 100 mol% of the total amount of metals other than lithium in the second positive electrode active material.
[0123] When the aluminum raw material is added to the aqueous solvent, the yttrium raw material is added together to coat Al and Y. The yttrium raw material may be, for example, yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide and / or (for example, any appropriate) combination thereof. The yttrium content (for example, amount) of the yttrium raw material in the second positive electrode active material based on the total amount of metals other than lithium of about 100 mol% can be designed to be about 0.05 mol% to about 1 mol%, for example, about 0.1 mol% to about 0.9 mol%, about 0.1 mol% to about 0.8 mol%, about 0.1 mol% to about 0.6 mol%, about 0.1 mol% to about 0.4 mol% or about 0.1 mol% to about 0.3 mol%. Each of the coating raw materials is designed within the above range to form (or provide) a coating having a substantially uniform and thin thickness of tens of nanometers to hundreds of nanometers, which can reduce the gas generation of the rechargeable lithium battery under high voltage operating conditions, and improve high capacity and long cycle life characteristics.
[0124] The solution in which the aluminum raw material and the optional yttrium raw material are mixed in an aqueous solvent may have a pH of about 1.5 to about 3.5 (e.g., about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2). The mixing and stirring of the lithium nickel manganese composite oxide and the aqueous solvent (in which the aluminum raw material and the yttrium raw material are mixed) may be performed for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5 (e.g., about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0). If these conditions are met, it is advantageous to form (or provide) a coating having a substantially uniform thickness.
[0125] Drying after the mixing process may be understood as a process for removing the solvent, and may be performed, for example, at about 40°C to about 240°C, about 100°C to about 220°C, or about 150°C to about 200°C. Reheating may be understood as a process for forming (or providing) a coating, and may be performed, for example, in an oxygen atmosphere at a temperature range of about 700°C to about 850°C, about 750°C to about 840°C, or about 800°C to about 830°C for about 2 hours to about 20 hours or about 3 to about 10 hours. In one or more embodiments, the reheating temperature may be lower than the previous heating temperature, and the reheating time may be equal to or shorter than the previous heating time. Under these conditions, reheating may be performed to obtain a desired or appropriate coating.
[0126] The first positive electrode active material, the second positive electrode active material, and the third positive electrode active material may be mixed to include about 60 wt% to about 90 wt% of the first positive electrode active material, about 5 wt% to about 35 wt% of the second positive electrode active material, and about 5 wt% to about 35 wt% of the third positive electrode active material based on a total of about 100 wt% of the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material. For example, the first positive electrode active material may be included in an amount of about 60 wt% to about 85 wt%, the second positive electrode active material may be included in an amount of about 10 wt% to about 25 wt%, and the third positive electrode active material may be included in an amount of about 5 wt% to about 20 wt%. Each of the positive electrode active materials may be mixed within the above ratios to maximize or increase energy density and increase capacity.
[0127] Positive electrode
[0128] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material. In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include other types (kinds) of positive electrode active materials. In addition, the positive electrode active material layer may optionally further include a binder, a conductive material and / or a combination thereof (e.g., any appropriate).
[0129] According to some embodiments, the loading level of the positive electrode active material layer may be about 10 mg / cm 2 ~ about 40mg / cm 2 , for example about 10 mg / cm 2 ~about 30mg / cm 2 or about 10 mg / cm 2 ~about 20mg / cm 2. In addition, the density of the positive electrode active material layer in the final pressed positive electrode may be about 3.4 g / cc to about 3.7 g / cc, for example, about 3.5 g / cc to about 3.6 g / cc or about 3.5 g / cc to about 3.58 g / cc. When the positive electrode active material according to some embodiments is applied, it is advantageous to achieve such a loading level and density of the positive electrode active material layer, and the positive electrode satisfying the loading level and density of the positive electrode active material layer within the above range is suitable for realizing a high-capacity, high-energy-density rechargeable lithium battery.
[0130] Binder
[0131] The binder improves the bonding properties between the positive electrode active material particles and between the positive electrode active material particles and the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin or nylon, but are not limited thereto.
[0132] Conductive Materials
[0133] A conductive material is included to provide electrode conductivity, and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials such as metal powder or metal fiber including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0134] Each content (eg, amount) of the binder and the conductive material may be about 0.5 wt % to about 5 wt % or about 0.5 wt % to about 3 wt % based on about 100 wt % of the positive electrode active material layer.
[0135] The positive electrode current collector may include Al, but the present disclosure is not limited thereto.
[0136] Rechargeable lithium battery
[0137] Some embodiments provide a rechargeable lithium battery including the aforementioned positive electrode, negative electrode, and electrolyte.
[0138] According to the shape, the rechargeable lithium batteries can be classified into cylindrical, prismatic, pouch, coin, etc. Figure 1 Schematic diagram showing a rechargeable lithium battery according to some embodiments. Figure 1, the rechargeable lithium battery 100 includes: an electrode assembly 40 manufactured by winding a separator 30 interposed between a positive electrode 10 and a negative electrode 20; and a case 50 accommodating therein the electrode assembly 40. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown).
[0139] The rechargeable lithium battery according to some embodiments may be rechargeable at a high voltage, or may be suitable for driving at a high voltage. For example, the upper charging voltage limit of the rechargeable lithium battery may be about 4.3V to about 4.6V or about 4.40V to about 4.55V. By applying the positive electrode active material according to some embodiments, the rechargeable lithium battery can significantly reduce the amount of gas generated even (for example, when) charging at a high voltage, and can achieve high capacity and long cycle life characteristics.
[0140] Negative electrode
[0141] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector and including a negative electrode active material, and the negative electrode active material layer may further include a binder, a conductive material, and / or (eg, any appropriate) combination thereof.
[0142] Negative electrode active material
[0143] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.
[0144] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, and / or (for example, any appropriate) combinations thereof as carbonaceous negative electrode active materials. Crystalline carbon may be amorphous or flaky, thin, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, etc.
[0145] Lithium metal alloys include alloys of lithium and one or more metals selected from (e.g., Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0146] The material capable of being doped / undoped with lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x(0<x≤2), Si-Q alloy (wherein Q is (for example, selected from) alkali metal, alkaline earth metal, 13th group element, 14th group element (excluding Si), 15th group element, 16th group element, transition metal, rare earth element and / or its (for example, any suitable) combination of elements, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po and / or its (for example, any suitable) combination) and / or its (for example, any suitable) combination. The Sn-based negative electrode active material may be Sn, SnO x (0<x≤2) (e.g., SnO2), Sn alloys, and / or (e.g., any suitable) combinations thereof.
[0147] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D 50 ) may be, for example, about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite may include silicon particles and amorphous carbon coated on the surface of the silicon particles (for example, it may be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles). For example, it may include secondary particles (cores) in which silicon primary particles are assembled and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon may also be present between silicon primary particles, for example, silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.
[0148] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core including crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite and / or (e.g., any appropriate) combination thereof. The amorphous carbon may include soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, etc.
[0149] When the silicon-carbon composite includes silicon and amorphous carbon, the content (e.g., amount) of silicon may be about 10 wt% to about 50 wt% and the content (e.g., amount) of amorphous carbon may be about 50 wt% to about 90 wt% based on about 100 wt% of the silicon-carbon composite. In one or more embodiments, if (e.g., when) the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, the content (e.g., amount) of silicon may be about 10 wt% to about 50 wt%, the content (e.g., amount) of crystalline carbon may be about 10 wt% to about 70 wt%, and the content (e.g., amount) of amorphous carbon may be about 20 wt% to about 40 wt% based on about 100 wt% of the silicon-carbon composite.
[0150] In addition, the thickness of the amorphous carbon coating layer may be about 5 nm to about 100 nm. The average particle size (D 50 ) may be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may exist as silicon alone, in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon may be SiO x (0<x≤2) represents. At this time, the atomic content (e.g., amount) ratio of Si:O (which indicates the degree of oxidation) may be about 99:1 to about 33:67. If (e.g., when) no definition is provided otherwise, the average particle size (D) as used herein is 50 ) indicates the diameter of particles where the cumulative volume in the particle size distribution is about 50 volume %.
[0151] The Si-based negative electrode active material or the Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material or the Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed and used, the mixing ratio may be about 1:99 to about 90:10 by weight.
[0152] Binder
[0153] The binder is used to bind the negative electrode active material particles well to each other and also to bind the negative electrode active material to the negative electrode current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder and / or (eg, any appropriate) combination thereof.
[0154] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, and / or (eg, any suitable) combinations thereof.
[0155] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenol resin, epoxy resin, polyvinyl alcohol and / or (e.g., any suitable) combination thereof.
[0156] When the aqueous binder is used as the negative electrode binder, a cellulose compound capable of imparting viscosity may be further included. As the cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and alkali metal salts thereof may be mixed and used. The alkali metal may be Na, K or Li.
[0157] The dry binder may be a polymer material capable of fiberization, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, and / or (eg, any appropriate) combinations thereof.
[0158] Conductive Materials
[0159] The conductive material is included to provide electrode conductivity (e.g., electron conductor), and any conductive material can be used as the conductive material unless it causes a chemical change. Examples of the conductive material include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials such as metal powder or metal fiber including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0160] The content (e.g., amount) of the negative electrode active material may be about 95 wt% to about 99.5 wt% based on about 100 wt% of the negative electrode active material layer, and the content (e.g., amount) of the binder may be about 0.5 wt% to about 5 wt% based on about 100 wt% of the negative electrode active material layer. For example, the negative electrode active material layer may include about 90 wt% to about 99 wt% of the negative electrode active material, about 0.5 wt% to about 5 wt% of the binder, and about 0.5 wt% to about 5 wt% of the conductive material.
[0161] current collector
[0162] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof, and may be in the form of foil, sheet or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 7 μm to about 10 μm.
[0163] Electrolyte
[0164] For example, the electrolyte for a rechargeable lithium battery may be an electrolyte that may include a non-aqueous organic solvent and a lithium salt.
[0165] The non-aqueous organic solvent is used as a medium for transporting ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent may include carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents and / or (for example, any appropriate) combinations thereof.
[0166] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In one or more embodiments, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles (such as R-CN (wherein R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, and may include a double bond, an aromatic ring or an ether bond, etc.)); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane, etc.); cyclopentane sulfone, etc.
[0167] The non-aqueous organic solvent may be used alone or in a mixture of two or more types (kinds), and if (for example, when) two or more types (kinds) are used in a mixed form, the mixing ratio may be appropriately adjusted according to the desired or appropriate battery performance, which is well known to those skilled in the art.
[0168] When the carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.
[0169] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate-based solvent and an aromatic hydrocarbon organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1 and used.
[0170] The electrolyte may further include vinyl ethylene carbonate, vinylene carbonate or ethylene carbonate-based compounds to improve the battery cycle life.
[0171] Examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0172] The lithium salt dissolved in the non-aqueous organic solvent supplies lithium ions in the battery, ensures the basic operation of the rechargeable lithium battery, and improves the transfer of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are integers from 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB) and lithium bis(oxalato)borate (LiBOB) (for example, at least one selected from the foregoing).
[0173] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. If the concentration of the lithium salt is within the above range, the electrolyte has suitable or appropriate ion conductivity and viscosity, and thus excellent or appropriate performance may be achieved, and lithium ions may be efficiently moved.
[0174] Diaphragm
[0175] Depending on the type or kind of rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, a multilayer film of two or more layers thereof, or a mixed multilayer film (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).
[0176] The membrane may include a porous substrate and a coating on (e.g., one or two (e.g., opposing) surfaces (e.g., at least one surface or at least one side or opposing surfaces or opposing sides) of the porous substrate, the coating comprising an organic material, an inorganic material and / or a combination thereof (e.g., any suitable combination).
[0177] The porous substrate may be a polymer film selected from any one of polymer polyolefins (such as polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyether ketones, polyarylether ketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fibers, TEFLON, and polytetrafluoroethylene, or may be a polymer film formed from a copolymer or mixture of two or more thereof.
[0178] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0179] The organic material may include a (meth)acryl-based copolymer, which includes: a first structural unit derived from (meth)acrylamide; and a second structural unit, including at least one of a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid or its salt.
[0180] The inorganic material may include (e.g., selected from) inorganic particles of Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and / or (e.g., any suitable) combination thereof, but the present disclosure is not limited thereto. The average particle size (D 50 ) may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.
[0181] An organic material and an inorganic material may be mixed in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.
[0182] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.
[0183] Embodiments and comparative examples of the present disclosure are described herein. However, the following examples are merely examples of the present disclosure, and the present disclosure is not limited to the following examples.
[0184] Example 1
[0185] 1. Preparation of positive electrode active material
[0186] (1) Preparation of the first positive electrode active material
[0187] Ni 0.75 Mn 0.23 Al 0.02 (OH)2 and LiOH are mixed in a molar ratio of about 1:1.05, and then preliminarily heat-treated at about 850°C in an oxygen atmosphere for about 8 hours to prepare a first composite oxide in the form of secondary particles having Li 1.05 Ni 0.75 Mn 0.23 Al 0.02 O2 composition and an average particle size of about 14 μm (D 50 ).
[0188] After aluminum sulfate is added to the distilled water solvent, the first composite oxide is added thereto, and then mixed and stirred for about 20 minutes to about 60 minutes. In this article, the aluminum content (e.g., amount) of aluminum sulfate is designed to be about 1.0 mol% based on the total amount of metals other than lithium of about 100 mol% in the first positive electrode active material. The solvent is removed from the mixed solution and then the residue is dried at about 190 ° C, after which zirconium oxide is dry mixed with it, and then, secondary heat treatment (i.e., reheating) is performed at about 825 ° C under an oxygen atmosphere for about 8 hours to obtain the first positive electrode active material. The zirconium content (e.g., amount) of zirconium oxide is designed to be about 0.2 mol% based on the total amount of metals other than lithium of about 100 mol% in the final first positive electrode active material. Figure 2 The average particle size (D 50 ) is about 14μm.
[0189] (2) Preparation of the Second Positive Electrode Active Material
[0190] Ni 0.75 Mn 0.25 (OH)2, LiOH and Al2O3 were mixed in a molar ratio of about 1:1:0.02 (i.e., the Al doping amount of Al2O3 was about 2.0 mol% based on about 100 mol% of the total amount of metal in the nickel-manganese-based composite hydroxide) and heat-treated at about 850°C for about 8 hours in an oxygen atmosphere to prepare a LiNi composite hydroxide in the form of individual particles with an average particle size (D50) of about 3 μm. 0.75 Mn 0.23 Al 0.02 A second composite oxide with a composition of O2.
[0191] After aluminum sulfate and yttrium nitrate are mixed in a distilled water solvent, a second composite oxide is added thereto, and then mixed and stirred for about 20 minutes to about 60 minutes. In this article, based on the total amount of metals other than lithium of about 100mol% in the final second positive electrode active material, the aluminum content (e.g., amount) of aluminum sulfate is designed to be about 0.4mol%, and the yttrium content (e.g., amount) of yttrium nitrate is designed to be about 0.1mol%. After removing the solvent from the mixed solution, the residue is dried at about 190°C and heat-treated (i.e., reheated) for about 8 hours at about 825°C under an oxygen atmosphere to prepare the second positive electrode active material. Figure 3 The average particle size (D 50 ) is about 3.5μm.
[0192] (3) Preparation of the Third Positive Electrode Active Material
[0193] Preparation of particles with an average particle size (D 50 ) is LiFePO4 (LFP) of primary particles of about 200 nm. Figure 4 is a SEM image of the third positive electrode active material.
[0194] (4) Preparation of the final positive electrode active material
[0195] About 70 wt % of the first positive electrode active material, about 20 wt % of the second positive electrode active material, and about 10 wt % of the third positive electrode active material were mixed to prepare a final positive electrode active material.
[0196] 2. Manufacturing of positive electrode
[0197] About 98.5wt% of the positive electrode active material, about 1.0wt% of the polyvinylidene fluoride binder and about 0.5wt% of the carbon nanotube conductive material are mixed to prepare a positive electrode active material layer slurry, and the slurry is coated on an aluminum foil current collector, and then dried and pressed to make a positive electrode. The density of the positive electrode active material layer in the final pressed positive electrode is about 3.46g / cc.
[0198] 3. Manufacturing of rechargeable lithium battery cells
[0199] About 97.5 wt% of graphite negative electrode active material, about 1.5 wt% of carboxymethyl cellulose and about 1 wt% of styrene-butadiene rubber in water solvent are mixed to prepare negative electrode active material layer slurry. The negative electrode active material layer slurry is coated on a copper foil current collector, then dried and pressed to make a negative electrode.
[0200] A rechargeable lithium battery cell was manufactured in a conventional manner using a polytetrafluoroethylene separator and an electrolyte prepared by dissolving about 1 M LiPF6 in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of about 3:7.
[0201] Example 2
[0202] The positive electrode and the rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the average particle size (D 50 ) is a LiMn primary particle of about 180 nm 0.6 Fe 0.4 PO4(LMFP) was used as the third positive electrode active material. Figure 5 2 is a SEM image showing the third positive electrode active material of Example 2.
[0203] Comparative Example 1
[0204] The positive electrode and the rechargeable lithium battery cell are manufactured in substantially the same manner as in Example 1, except that a mixture of about 80 wt % of the first positive electrode active material and about 20 wt % of the third positive electrode active material is used as the positive electrode active material without using the second positive electrode active material.
[0205] Comparative Example 2
[0206] The positive electrode and the rechargeable lithium battery cell are manufactured in substantially the same manner as in Example 2, except that a mixture of about 80 wt % of the first positive electrode active material and about 20 wt % of the third positive electrode active material is used as the positive electrode active material without using the second positive electrode active material.
[0207] Comparative Example 3
[0208] The positive electrode and the rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that a mixture of about 70 wt % of the first positive electrode active material and about 30 wt % of the second positive electrode active material was used as the positive electrode active material without using the third positive electrode active material.
[0209] For better understanding, the design details of the positive electrode active materials of Examples and Comparative Examples are briefly shown in Table 1.
[0210] Table 1
[0211]
[0212]
[0213] Evaluation Example 1
[0214] The rechargeable lithium battery cells of the embodiments and comparative examples were charged at a constant current of about 0.2C to an upper limit voltage of about 4.45V, and charged at a constant voltage of about 0.05C, and then discharged at about 0.2C to a cutoff voltage of about 3.0V at about 25°C for initial charging and discharging, and the initial discharge capacity results are shown in Table 1. Subsequently, the battery cells were charged at about 1.0C in a voltage range of about 3.0V to about 4.45V at about 45°C and discharged at about 1.0C for about 50 times or more, and then the ratio of the 50th cycle discharge capacity to the initial discharge capacity was calculated as the cycle life, which is then shown in Table 1.
[0215] In one or more embodiments, the density of the positive electrode active material layer in the final pressed positive electrodes of Examples and Comparative Examples is shown in Table 1.
[0216] Referring to Table 1, compared to the comparative example, if (for example, when) driven at a high voltage of about 4.45 V, the positive electrodes of the embodiments each exhibit a relatively high density of the positive electrode active material layer and excellent or appropriate capacity characteristics and cycle life characteristics. Compared to the embodiment, if (for example, when) driven at a high voltage of about 4.45 V, Comparative Examples 1 and 2 each exhibit a relatively low density of the positive electrode active material layer and a relatively low initial discharge capacity.
[0217] The battery management system (BMS) device and / or any other related device or component according to the embodiments of the present invention described herein may be implemented using any appropriate hardware, firmware (e.g., a dedicated integrated circuit), software, or a combination of software, firmware, and hardware. For example, the various components of the device may be formed on an integrated circuit (IC) chip or on a separate IC chip. In addition, the various components of the device may be implemented on a flexible printed circuit film, a tape carrier package (TCP), or a printed circuit board (PCB), or formed on a substrate. In addition, the various components of the device may be processes or threads running on one or more processors in one or more computing devices, executing computer program instructions and interacting with other system components to perform the various functions described herein. The computer program instructions are stored in a memory, which may be implemented in a computing device using a standard memory device, such as, for example, a random access memory (RAM). The computer program instructions may also be stored in other non-temporary computer-readable media (such as, for example, a CD-ROM, a flash drive, etc.). Moreover, those skilled in the art should recognize that, without departing from the scope of the present disclosure, the functions of various computing devices may be combined or integrated into a single computing device, or the functions of a dedicated computing device may be distributed on one or more other computing devices.
[0218] In the present disclosure, "does not include one or any 'component'", "excludes one or any 'component'", "no 'component'" and the like mean that the "component" is not added, selected or used as a component in the composition / structure, but due to other impurities and / or external factors, the "component" may still be included in less than an appropriate amount.
[0219] While the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it is to be understood that the present disclosure is not limited to the disclosed embodiments, but is intended to cover one or more suitable modifications and equivalent arrangements included within the spirit and scope of the claims.
Claims
1. A positive electrode active material comprising: a first positive electrode active material comprising a lithium nickel manganese-based composite oxide having a nickel content of 60 mol% or more based on 100 mol% of the total amount of metals other than lithium and comprising secondary particles made by aggregating a plurality of primary particles, wherein the secondary particles have an average particle size of 10 μm to 20 μm; a second positive electrode active material comprising a lithium nickel manganese-based composite oxide having a nickel content of greater than or equal to 60 mol % based on 100 mol % of the total amount of metals other than lithium and comprising individual particles, wherein the average particle size of the individual particles is 2 μm to 8 μm; and A third positive electrode active material includes particles comprising a lithium transition metal phosphate.
2. The positive electrode active material according to claim 1, wherein The average particle size of the particles of the third positive electrode active material is 10 nm to 2 μm.
3. The positive electrode active material according to claim 1, wherein Based on a total of 100 wt % of the first positive electrode active material, the second positive electrode active material and the third positive electrode active material, the first positive electrode active material is included in an amount of 60 wt % to 90 wt %, the second positive electrode active material is included in an amount of 5 wt % to 35 wt %, and the third positive electrode active material is included in an amount of 5 wt % to 35 wt %.
4. The positive electrode active material according to claim 1, wherein The lithium nickel manganese composite oxide of the first positive electrode active material and the lithium nickel manganese composite oxide of the second positive electrode active material are the same as or different from each other, and the nickel content is independently 60 mol% to 80 mol% based on 100 mol% of the total amount of metals other than lithium.
5. The positive electrode active material according to claim 1, wherein The lithium nickel manganese-based composite oxide of the first positive electrode active material and the lithium nickel manganese-based composite oxide of the second positive electrode active material each independently include a lithium nickel manganese aluminum-based composite oxide further including aluminum in addition to nickel and manganese, and The aluminum content in the lithium nickel manganese aluminum-based composite oxide is 0.1 mol% to 3 mol% based on 100 mol% of the total amount of metals other than lithium.
6. The positive electrode active material according to claim 1, wherein The lithium nickel manganese composite oxide of the first positive electrode active material, the lithium nickel manganese composite oxide of the second positive electrode active material, and the lithium transition metal phosphate of the third positive electrode active material each independently have a cobalt content less than or equal to 0.01 mol % based on 100 mol % of the total amount of metals other than lithium.
7. The positive electrode active material according to claim 1, wherein The lithium nickel manganese composite oxide of the first positive electrode active material and the lithium nickel manganese composite oxide of the second positive electrode active material are each independently represented by Chemical Formula 1: Chemical formula 1 Li a1 Ni x1 Mr y1 Al z1 M 1 w1 O 2-b1 X b1 in, In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S.
8. The positive electrode active material according to claim 7, wherein In Chemical Formula 1, 0.6≤x1≤0.8, 0.1≤y1≤0.39, 0.01≤z1≤0.03, and 0≤w1≤0.29 are satisfied.
9. The positive electrode active material according to claim 1, wherein The first positive electrode active material further includes a coating layer containing aluminum on the surface of the secondary particles, and The aluminum content of the coating layer is 0.1 mol% to 2 mol% based on 100 mol% of the total amount of metals other than lithium in the first positive electrode active material.
10. The positive electrode active material according to claim 9, wherein The coating further includes zirconium, yttrium, or a combination thereof.
11. The positive electrode active material according to claim 10, wherein The coating layer further includes 0.05 mol % to 1 mol % of zirconium and / or 0.05 mol % to 1 mol % of yttrium based on 100 mol % of the total amount of metals other than lithium in the first positive electrode active material.
12. The positive electrode active material according to claim 9, wherein The coating layer of the first positive electrode active material includes a shell continuously surrounding the surface of each of the secondary particles.
13. The positive electrode active material according to claim 9, wherein The coating layer of the first positive electrode active material has a thickness of 30 nm to 500 nm.
14. The positive electrode active material according to claim 9, wherein The first positive electrode active material further includes a grain boundary coating portion containing aluminum on the surface of the primary particle inside each of the secondary particles.
15. The positive electrode active material according to claim 1, wherein The second positive electrode active material further includes a coating layer containing aluminum on the surface of the single particle, and The aluminum content of the coating layer is 0.1 mol% to 2 mol% based on 100 mol% of the total amount of metals other than lithium in the second positive electrode active material.
16. The positive electrode active material according to claim 15, wherein The coating layer of the second positive electrode active material includes a shell continuously surrounding the surface of each of the individual particles.
17. The positive electrode active material according to claim 15, wherein The coating layer of the second positive electrode active material has a thickness of 30 nm to 500 nm.
18. The positive electrode active material according to claim 15, wherein The coating of the second positive electrode active material further comprises yttrium, and The yttrium content of the coating layer is 0.1 mol% to 1 mol% based on 100 mol% of the total amount of metals other than lithium in the second positive electrode active material.
19. The positive electrode active material according to claim 18, wherein In the coating layer of the second positive electrode active material, The aluminum is present in the form of a continuous film and the yttrium is present in the form of islands.
20. The positive electrode active material according to claim 18, wherein The second positive electrode active material comprises: A first coating layer located on the surface of the single particle and containing aluminum; and a second coating layer located on the first coating layer and containing yttrium.
21. The positive electrode active material according to claim 1, wherein The lithium transition metal phosphate of the third positive electrode active material includes lithium iron phosphate, lithium manganese iron phosphate, lithium manganese phosphate, lithium titanium phosphate or a combination thereof.
22. The positive electrode active material according to claim 1, wherein The lithium transition metal phosphate of the third positive electrode active material is represented by Chemical Formula 3, Chemical Formula 4, Chemical Formula 5, Chemical Formula 6 or Chemical Formula 7: Chemical formula 3 Li a3 Fe (1-x3) M 3 x3 PO4, In Chemical Formula 3, 0.90≤a3≤1.5, 0≤x3≤0.4, and M 3 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr or a combination thereof, Chemical formula 4 Li a4 Mn x4 Fe (1-x4-y4) M 4 y4 PO4, In Chemical Formula 4, 0.90≤a4≤1.5, 0.1≤x4≤0.9, 0≤y4≤0.4, and M 4 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr or a combination thereof, Chemical formula 5 Li a5 Mn (1-x5) M 5 x5 PO4, In Chemical Formula 5, 0.90≤a5≤1.5, 0≤x5≤0.4, and M 5 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr or a combination thereof, Chemical formula 6 Li a6 You (2-x6) M 6 x6 (PO4)3, In Chemical Formula 6, 0.90≤a6≤1.5, 0≤x6≤0.4, and M 6 is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr or a combination thereof, Chemical formula 7 Li a7 You (1-x7) M 7 x7 PO5, In Chemical Formula 7, 0.90≤a7≤1.5, 0≤x7≤0.4, and M 7 It is Al, Ca, Ce, Cr, Cu, La, Mg, Mo, Nb, Ni, Sn, Sr, V, W, Y, Zn, Zr or a combination thereof.
23. The positive electrode active material according to claim 1, wherein The lithium transition metal phosphate of the third positive electrode active material includes LiFePO4, LiMn 0.7 Fe 0.3 PO4、LiMn 0.6 Fe 0.4 PO4、LiMn 0.5 Fe 0.5 PO4、LiMn 0.4 Fe 0.6 PO4、LiMn 0.3 Fe 0.7 PO4, LiMnPO4, LiTiPO5, LiTi2(PO4)3 or a combination thereof.
24. A positive electrode comprising a positive electrode current collector, and a positive electrode active material layer on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 23.
25. The positive electrode of claim 24, wherein The positive electrode active material layer has a density of 3.4 g / cc to 3.7 g / cc.
26. A rechargeable lithium battery comprising: The positive electrode according to claim 24 or 25, negative electrode, and Electrolyte.
27. The rechargeable lithium battery of claim 26, wherein The upper charging voltage limit of the rechargeable lithium battery is 4.3V to 4.6V.
Citation Information
Cited By
Lithium ion secondary battery and electric device
CN121769203A